Porous fibers surface decorated with nanofillers: From melt‐spun PP/PVA blend fibers with silica nanoparticles. Issue 11 (4th September 2019) - Yan, Xiang; Cayla, Aurélie; Salaün, Fabien; Devaux, Eric; Liu, Pengqing; Mao, Jianzhao; Huang, Tingjian
ABSTRACT: Biphasic polypropylene (PP)‐polyvinyl alcohol (PVA) fibers containing silica nanoparticles with various surface hydrophobicity were melt‐spun. The localization of nanoparticles relates on the thermodynamic factors, and the design promotes a surface‐decorated fibrous scaffold with nanoparticles after selective extraction. The influence of silica nanoparticles on the melt flow index was observed, and the interface‐located Aerosil R972 silica nanoparticles lead to an increase in viscosity. The scanning electron microscopy (SEM) demonstrates the preponderant interfacial localization of Aerosil R972 nanoparticles within the biphasic fibers. The porous morphology of the obtained fibers was investigated by SEM, selective extraction experiment, X‐ray diffraction analysis, and dynamical mechanical analysis. The specific interface area of PP70 ‐PVA30 fibers with a draw ratio (DR) of 2 is 3.2 m 2 g −1 and is further enlarged with the increase of DR. The incorporation of nanoparticles contributes to the increase of interconnectivity of the PVA phase. The further increment of DR modifies the crystalline structure, and results in better mechanical properties. The Aerosil R972‐containing fibers with the DR of 3 provide almost completely accessible PVA phase, with enough mechanical strength to be transformed into textile products, and retains a good mechanical property after selective extraction. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48470. Abstract : Fabrication of polypropylene porous fibers surface decorated with silica nanoparticles